2020
DOI: 10.1039/c9cp06468k
|View full text |Cite
|
Sign up to set email alerts
|

Stability of the chaperonin system GroEL–GroES under extreme environmental conditions

Abstract: The chaperonin system GroEL–GroES rescues proteins from improper folding at external stress conditions up to 70 °C and pressures of 1 kbar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
(97 reference statements)
1
6
0
Order By: Relevance
“…The partial unfolding of the GroEL 14 complexes may be potentially due to SEC‐driven depletion of critical cofactor ions, e.g., Mg 2+ and K + ions that are present in a free‐state in the buffer solution, in which the GroEL 14 sample was diluted, or that diffused out from the cation binding pockets of GroEL 14 into the mobile phase during the SEC fractionation. As reported in numerous structural biology studies [ 7 , 50 , 51 , 52 , 53 ] and demonstrated in our presented work (see below), Mg 2+ and K + ions have a fundamental role in the stabilization and folding of the GroEL 14 complexes. The applied CE–MS conditions allowed us to maintain the structural integrity of the injected GroEL 14 non‐covalent complexes with coordinated cofactors in a medium enriched with these necessary metal ions.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…The partial unfolding of the GroEL 14 complexes may be potentially due to SEC‐driven depletion of critical cofactor ions, e.g., Mg 2+ and K + ions that are present in a free‐state in the buffer solution, in which the GroEL 14 sample was diluted, or that diffused out from the cation binding pockets of GroEL 14 into the mobile phase during the SEC fractionation. As reported in numerous structural biology studies [ 7 , 50 , 51 , 52 , 53 ] and demonstrated in our presented work (see below), Mg 2+ and K + ions have a fundamental role in the stabilization and folding of the GroEL 14 complexes. The applied CE–MS conditions allowed us to maintain the structural integrity of the injected GroEL 14 non‐covalent complexes with coordinated cofactors in a medium enriched with these necessary metal ions.…”
Section: Resultssupporting
confidence: 76%
“…In the presence of ATP and GroES, one unfolded SP at a time would be encapsulated for ≈10 s in the nano‐cage formed by the GroEL–GroES complex for folding or refolding. [ 4 , 5 , 6 , 7 ] Importantly, ATP binding and ATP hydrolysis to adenosine diphosphate (ADP) induce drastic conformational rearrangements of the apical and intermediate domains of each GroEL subunit, which results in a twofold increase of the central cage volume. Characterizing these conformational changes in solution is technically challenging because they represent intermediate states that are sporadically and intermittently populated.…”
Section: Introductionmentioning
confidence: 99%
“…The GroEL-GroES complex plays a key role in protein folding and comprises two heptameric rings of GroEL (forming a cavity) and a heptameric ring of GroES (acting as a lid). Unfolded substrate proteins will be able to enter the cavity and upon ATP hydrolysis will be folded before being released . Importantly, it has been shown that upon over-expression this complex promotes tolerance to aminoglycoside antibiotics in E.…”
Section: Resultsmentioning
confidence: 99%
“…N. europaea exhibited the least amount of DEGs coding for ROS detoxification and general stress response proteins, while C. testosteroni , particularly in the tripartite culture, displayed the highest responsiveness. DNA repair mechanisms and chaperones like the GroES-GroEL system, a heat shock protein complex known to be induced in stress conditions to avoid protein aggregation and misfolding, 36 were most commonly upregulated across strains. However, the expression of DNA repair-related genes was ambiguous across the strains.…”
Section: Discussionmentioning
confidence: 99%